1992
DOI: 10.1016/s0022-5347(17)37240-3
|View full text |Cite
|
Sign up to set email alerts
|

Intravesical Instillations of 4-EPI-Doxorubicin (Epirubicin) in the Prophylactic Treatment of Superficial Bladder Cancer: Results of a Controlled Prospective Study

Abstract: A controlled prospective study in 65 patients was done to evaluate the efficacy of intravesical epirubicin administration as prophylactic treatment in regard to the pattern of tumor recurrences after complete endoscopic resection of superficial transitional cell carcinoma of the bladder. Intravesical instillations of the drug were given weekly for 6 consecutive weeks and to the responders an intermittent maintenance therapy was administered for the first 2 years after each followup examination. Of the patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
20
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 13 publications
1
20
0
Order By: Relevance
“…In one reported study, epirubicin yielded superior therapeutic responses and a lower toxicity profile because it is more lipophilic than doxorubicin [15]. Melekos et al [16] reported that 60-63% of patients treated with epirubicin after TUR remained free of recurrence [17,18]. Recently, 122 patients were studied for their response to a high (2 mg/ml) or standard (1 mg/ml) dose of epirubicin for the treatment of superficial bladder cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…In one reported study, epirubicin yielded superior therapeutic responses and a lower toxicity profile because it is more lipophilic than doxorubicin [15]. Melekos et al [16] reported that 60-63% of patients treated with epirubicin after TUR remained free of recurrence [17,18]. Recently, 122 patients were studied for their response to a high (2 mg/ml) or standard (1 mg/ml) dose of epirubicin for the treatment of superficial bladder cancer [19].…”
Section: Discussionmentioning
confidence: 99%
“…These results are similar to those reported for other intravesical prophylactic chemotherapy. 4,5,11 Previous studies of recurrence using the surveillance protocol have demonstrated that the recurrence-free rate is approximately 40-50% at 2-3 years and < 30% at 5 years after operation. 2,17,19 In the present study, we did not have a control group in whom chemotherapeutic agents were not administered.…”
Section: Discussionmentioning
confidence: 99%
“…10 Administration schedules for intravesical epirubicin vary. [11][12][13] We have used low-dose epirubicin (20 mg/instillation) in order to reduce adverse reactions and have already reported a satisfactory prophylactic effect. 14 In the present study, we limited the subjects to patients with primary tumors and analyzed the prognostic factors related to tumor recurrence.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence, however, from previous controlled trials suggests that intracavitary chemotherapy, including epirubicin. has failed to reduce disease progression [3,6,7,[10][11][12]18]. In contrast, few randomized studies have shown that the achieved benefits of adjuvant BCG treatment can be translated into a prolonged decrease in the rate of disease progression [3.…”
Section: Discussionmentioning
confidence: 99%
“…Epirubicin (4'-epi-doxorubicin) was synthesized with the aim of finding new anthracycline analogues with an improved spectrum of antitumour activity and lower toxicity. Indeed, the antitumour effica cy of this drug has been proved against a variety of neo plasms when used by the intravenous route, with at least similar effects with its parent Adriamycin but with lower toxicity [4], Epirubicin is also effective in preventing tumour recurrences when given intravesicallv to patients with superficial bladder disease [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%